Early Mental Health and Quality of Life in Discharged Patients With COVID-19 - Hu, Jinzhuo; Zhang, Yang; Xue, Qingqing; Song, Yun; Li, Fei; Lei, Ran; Wu, Jinlun; Qian, Jinghua (Frontiers in Public Health, 2021)
Aim: This study aims to analyze the early mental health and quality of life of discharged patients with coronavirus disease 2019(COVID-19), which can also provide a scientific basis for the further development of intervention progroms. Methods: Totally 108 subjects participated in this study, including the experimental group (90 patients diagnosed with COVID-19 from March to April 2020 and hospitalized in Wuhan China Resources & Wisco general hospital, 83.3%) and the control group (18 healthy participants, 16.7%). Their mental health and quality of life were measured through 12-item Short Form Health Survey version 2(SF-12v2), the Self-rating anxiety scale(SAS), the Self-rating depression scale(SDS) and the International Physical Activity Questionnaire(IPAQ). The results of questionnaires were compared between these two groups. Results:①Comparison of anxiety status: Among 90 COVID-19 discharged patients, 30 patients(33.3%) had a state of anxiety. Compared with the healthy population, COVID-19 patients in the early stages of discharge had a higher incidence of anxiety and more severe anxiety symptoms(P<0.05). ②Comparison of depression status: Among 90 COVID-19 discharged patients, 29 patients(32.2%) had a state of depression. Compared with the healthy population, COVID-19 patients in the early stages of discharge had a higher incidence of depression and more severe depression symptoms(P<0.05). ③Comparison of quality of life: 78 patients(86.7%) presented a decrease in physical health-related quality of life and 73 patients (81.1%) presented a decrease in psychology-related quality of life. The SF-12v2 physical component summary(PCS) and the SF-12v2 mental component summary(MCS) of patients were significantly lower than those of the healthy people, especially in physical function (PF), vitality (VT), social function (SF) and mental health (MH)(All P<0.05). Conclusion: During the early phase after discharged, patients with COVID-19 might experience negative emotions such as anxiety or depression and also had problems with reduced quality of life. Therefore, the intervention plan should focus on strengthening psychological condition and improving physical function, so as to adjust the psychological state and improve the quality of life.